1994
DOI: 10.1111/j.1445-2197.1994.tb02279.x
|View full text |Cite
|
Sign up to set email alerts
|

The Safety of Elective Liver Resection in a Special Unit

Abstract: The benefit of hepatic surgery for benign or malignant conditions is a balance between peri-operative morbidity/mortality and long-term potential for cure or palliation. The aim of this retrospective study was to illustrate that the safety of liver resection is a function of the frequenty of performance of the procedure. Between 1973 and 1992, 327 elective liver resections were performed. The indication for surgery was malignant tumour in 275 cases of which 170 (62%) and 105 (38%) were for metastatic and prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 18 publications
5
13
0
1
Order By: Relevance
“…All transfused patients (6%) received autologous blood transfusion, but it should be noted that the same resection procedures performed by an open approach would probably not have required blood transfusion. The need for blood transfusion in minor liver resections on a noncirrhotic liver parenchyma is indeed minimal when using an open approach [63][64][65]. This feature confirmed that bleeding remains the most important intraoperative problem during liver resection, as in open surgery, but is obviously more difficult to control laparoscopically, even for minor resections.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…All transfused patients (6%) received autologous blood transfusion, but it should be noted that the same resection procedures performed by an open approach would probably not have required blood transfusion. The need for blood transfusion in minor liver resections on a noncirrhotic liver parenchyma is indeed minimal when using an open approach [63][64][65]. This feature confirmed that bleeding remains the most important intraoperative problem during liver resection, as in open surgery, but is obviously more difficult to control laparoscopically, even for minor resections.…”
Section: Discussionsupporting
confidence: 50%
“…However, in this selected group of patients, when the technique is appropriately performed by an expert surgical team, the technique appears to be safe, with a low morbidity and a short postoperative hospital stay. However, it should be remembered that open resectional liver surgery has achieved a significant reduction in postoperative morbidity, especially for minor liver resections [64,65]. Additional comparative studies are needed to evaluate the benefit of the laparoscopic approach in terms of postoperative recovery.…”
Section: Discussionmentioning
confidence: 99%
“…9 Data regarding safety of hepatic resection by experienced hepatobiliary surgeons similarly support this approach. 10,11 Evaluation of patients for resectability of colorectal cancer demands thorough cancer staging. Rapidsequence CT imaging of the chest and whole abdomen is the preferred technique.…”
Section: Discussionmentioning
confidence: 99%
“…However, laparoscopic liver surgery has been slow to develop because of perceived technical difficulties. The gradual trend toward bloodless surgery in traditional techniques of hepatic resection, 17,18 greater experience with laparoscopic surgery, and improvements in video equipment, laparoscopic instrumentation, and surgical skills have led hepatobiliary surgeons to attempt laparoscopic management of various hepatic lesions. 6,9,19 Management of biliary cysts offers good training for laparoscopic liver surgery.…”
Section: Discussionmentioning
confidence: 99%